Effect of Aluminum Doping on the Performance and Microstructure of Methyl-Modified SiO2 Sol. Issue 207 (3rd May 2020) - Yang, Jing; Xu, Zhirun; Mu, Ruihua; Zhao, Yamei; Li, Bo; Hou, Haiyun
Abstract: With methyltriethoxysilane as hydrophobic precursors and aluminum isopropoxide as the aluminum source, the Al2 O3 /SiO2 sols and their gel materials were prepared. The effects of aluminum content ( nAl ) on the viscosity ( η ), density ( ρ ), reaction rate constant ( k ), Gibbs energies of activation for viscous flow ( ΔG *), particle size of Al2 O3 /SiO2 sols were studied. And the high temperature calcined materials were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and Scanning electron microscopy (SEM). The results show that, with the increase of nAl, the η, n and ΔG * values of the Al2 O3 /SiO2 sols decrease while the k and ρ values and average particle sizes increase. There is strong intermolecular interaction between the Al2 O3 and SiO2 sol molecules. The Al-O-Si bond exists in the Al2 O3 /SiO2 materials before and after calcination at 350 °C. Calcination at 350 °C in N2 atmosphere can change the phase structure of Al2 O3 /SiO2 sample greatly, which can make the γ -AlOOH in the Al2 O3 /SiO2 gel material convert to γ -Al2 O3 through dehydration.